Professionalism as social responsibility in procurement and administration. Issue 3 (8th May 2017) - Steinfeld, Joshua; McCue, Clifford; Prier, Eric
Abstract : Purpose: The purpose of this empirical study is to identify the job tasks where decisions regarding social responsibility are likely to occur and assess the potential connections between social responsibility and professionalism. Design/methodology/approach: A job study conducted by the Universal Public Procurement Certification Council (UPPCC) of 2, 593 practitioners is used for data collection. Factor analysis is applied to a set of 75 procurement job tasks to determine the relationship between practitioners' performance and management of job tasks and social responsibility variables. Findings: The results suggest that there are specific job tasks performed and managed in both public and private sector procurement that share a unique relationship with social responsibility variables. Research limitations/implications: The manuscript advances the research on professionalism in procurement and administration through empirically testing job tasks performed and managed by practitioners and identifying relationships between job tasks according to a professional orientation toward social responsibility. Practical implications: The study shows that specific job tasks are performed and managed in procurement and administration with a social responsibility consideration. Social implications: The technical nature of job tasks found to be related to social responsibility suggests a paradoxical view of the politics-administration dichotomy, and the notion that neutral tasks of both the public and private sectors are not void of a social function. Originality/value: One attribute of professionalism in the literature, social responsibility, is operationalized through actual performance and management of job tasks by practitioners.